2016
DOI: 10.3390/ijerph13040442
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Thyroid Nodules and an Analysis of Related Lifestyle Factors in Beijing Communities

Abstract: Thyroid nodules (TNs) have annual increasing trends worldwide, and large-scale investigations on the prevalence of TNs in Beijing communities have not been conducted since the introduction of salt iodization in 1995. We performed a cross-sectional study to determine the prevalence of TNs, their epidemiological characteristics, and their correlation with lifestyle factors. A total of 6324 permanent residents aged 18 years or older (mean age, 52.15 ± 11.58 years) from seven representative communities in Beijing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
98
4
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(122 citation statements)
references
References 55 publications
13
98
4
7
Order By: Relevance
“…The gender disparity of the presence of TNs was in accordance with previous studies [5,19,20]. Interestingly, this study found a higher odds ratio of TNs (3.36, 95%CI = 1.97-5.75; P < 0.001) in females than previous studies, which indicates a potentially increasing trend of gender disparity on TNs with aging.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The gender disparity of the presence of TNs was in accordance with previous studies [5,19,20]. Interestingly, this study found a higher odds ratio of TNs (3.36, 95%CI = 1.97-5.75; P < 0.001) in females than previous studies, which indicates a potentially increasing trend of gender disparity on TNs with aging.…”
Section: Discussionsupporting
confidence: 91%
“…The associations between TNs and hypertension as well as diabetes have been reported in general population [8,23,24]. Previous studies have investigated the relationship between obesity and TNs, indicating that people who were overweight and with a higher BMI were more likely to have TNs than those who were not [5,21,25]. In centenarians, approximately half of them were underweight (53.0%) and another half were mainly normal weight (47.0%).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations